Biological Potential and Bioaccessibility of Encapsulated Curcumin into Cetyltrimethylammonium Bromide Modified Cellulose Nanocrystals - Casanova, Francisca; Pereira, Carla F.; Ribeiro, Alessandra B.; Castro, Pedro M.; Freixo, Ricardo; Martins, Eva; Tavares-Valente, Diana; Fernandes, João C.; Pintado, Manuela E.; Ramos, Óscar L. (Pharmaceuticals (Basel, Switzerland), 2023)
Curcumin is a natural phenolic compound with important biological functions. Despite its demonstrated efficacy in vitro, curcumin biological activities in vivo are dependent on its bioaccessibility and bioavailability, which have been highlighted as a crucial challenge. Cetyltrimethylammonium bromide-modified cellulose nanocrystals (CNC-CTAB) have been shown to be effective in curcumin encapsulation, as they have the potential to enhance biological outcomes. This study evaluated the biological effects of curcumin encapsulated within CNC-CTAB structures, namely its antioxidant, anti-inflammatory and antimicrobial properties, as well as the release profile under digestion conditions and intestinal permeability. Encapsulated curcumin demonstrated antioxidant and anti-inflammatory properties, effectively reducing reactive oxygen species and cytokine production by intestinal cells. The delivery system exhibited antimicrobial properties against Campylobacter jejuni bacteria, further suggesting its potential in mitigating intestinal inflammation. The system showed the ability to protect curcumin from degradation and facilitate its interaction with the intestinal epithelium, highlighting the potential of CNC-CTAB as carrier to enhance curcumin intestinal biological functions.